Religious Explanations for Environmental Degradation in Narikoso, Fiji - Bertana, Amanda (Understanding Climate Change through Religious Lifeworlds, 2021)
How can religion help to understand and contend with the challenges of climate change?Understanding Climate Change through Religious Lifeworld,edited by David Haberman, presents a unique collection of essays that detail how the effects of human-related climate change are actively reshaping religious ideas and practices, even as religious groups and communities endeavor to bring their traditions to bear on mounting climate challenges.People of faith from the low-lying islands of the South Pacific to the glacial regions of the Himalayas are influencing how their communities understand earthly problems and develop meaningful responses to them. This collection focuses on a variety of different aspects of this critical interaction, including the role of religion in ongoing debates about climate change, religious sources of environmental knowledge and how this knowledge informs community responses to climate change, and the ways that climate change is in turn driving religious change.Understanding Climate Change through Religious Lifeworlds offers a transnational view of how religion reconciles the concepts of the global and the local and influences the challenges of climate change.
Keywords: dept.soc

Race: Readings on Identity, Ideology, and Inequality - Meyerhoffer, Cassi (Cognella anthology series for teaching, 2021)
Keywords: Race awareness; Race relations; United States; Racism; United States; United States; dept.soc; faculty_collection

Poverty, Racism, & Sexism: The Reality of Oppression in America - Doob, Christopher Bates (Routledge, Taylor & Francis Group, 2021)
"Exploring the structural causes and consequences of inequalities based on a person's race, class, and gender, Poverty, Racism & Sexism: The Reality of Oppression in America concentrates on this formidable set of disadvantages, demonstrating how Americans are adversely affected by just one or a combination of three social factors. Grounded in sociological thought, the text highlights unfolding stories about major social inequalities and relentless campaigns for people's rights. Weaving together such concepts as individualism, social reproduction, social class, and intersectionality, the book provides a framework for readers to understand the vast injustices these groups encounter, where and why they originated, and why they continue to endure. Poverty, Racism & Sexism is a compact, versatile volume which will prove an invaluable resource for those studying social inequality, social problems, social stratification, contemporary American society, social change, urban sociology, and poverty and inequality"--
Keywords: Equality; Race relations; United States; Poverty; United States; Racism; United States; Sexism; United States; United States; dept.soc; faculty_collection

“On the street, the only person you gotta bow down to is yourself”: Masculinity, homelessness, and incarceration - Umamaheswar, Janani (Justice Quarterly, 2021)
Despite the well-established link between homelessness and incarceration, very little qualitative research has focused on the social processes that underlie this nexus. In this article, I draw on 19 in-depth interviews with incarcerated men who reported pre-prison housing instability, supplemented with 5 interviews with formerly-incarcerated men experiencing homelessness, to explore the gendered nature of the homelessness-incarceration nexus. I propose the concept of “liberative instability”—defined as an unfettered lifestyle characterized by double-edged freedom and independence—to explore the changing meaning of homelessness in men’s narratives of their life course. Additionally, I explore how themes of masculinity and liberative instability are embedded in men’s narratives of freedom and confinement as they reflect on their experiences with homelessness and incarceration. These findings animate existing quantitative research by highlighting that the homelessness-incarceration nexus cannot be understood fully or disrupted without considering the significance of age-graded cultural scripts regarding masculinity. © 2021 Academy of Criminal Justice Sciences.
Keywords: Homelessness; dept.soc; incarceration; masculinity; peer-reviewed; the life course

“When my mother died, I think a part of me died:” maternal fusion and the relationship between incarcerated men and their mothers - Umamaheswar, J. (Journal of Family Issues, 2021)
Drawing on theoretical literature on the mothering discourse, I explore how incarcerated men give meaning to their relationships with their mothers. Using 24 in-depth interviews with incarcerated adult men, I argue that adherence to the mothering discourse results in sons holding their mothers’ maternal practices to impossibly high standards while simultaneously feeling obligated to reconcile with their mothers even when doing so is tremendously difficult. I also advance the concept of “maternal fusion”—the process through which the identities of mothers and their children are intertwined—to examine how incarcerated adult sons reproduce gendered mothering ideologies in their narratives of (a) negative early childhood and adolescent relationships with their mothers and (b) reconciliation as they reflect on their relationships with their mothers as adult sons.
Keywords: adolescent; adult; article; child; childhood; dept.soc; dept.swk; drawing; female; human; human experiment; ideology; incarceration; infant; interview; male; maternal fusion; mother; mothering; mothering discourse; narrative; peer-reviewed; theoretical study